Meeting International Standards for Medical Device Reliability and Risk Management - Gullola, Ubaydullayeva (American Journal of Botany and Bioengineering, 2024)
In the design and development of safe, effective medical devices, reducing risk and ensuring reliability are a manufacturer’s primary responsibility. The advanced technology inherent in medical devices and their production means that all aspects of the system–including mechanics, electronics, software, and hardware–must be evaluated for reliability. What’s more, due to the significant impact that a new medical device technology can have on human lives, every aspect of its development–from design and prototyping through manufacture, distribution, disposal, and decommissioning–must adhere to strict quality standards that are documented and traceable to functional and safety requirements. These standards may apply not only to manufacturers, but also to vendors, suppliers, contractors, OEMs, third parties, and others in product development and distribution.